EasyService Car Service Booking System - THIAGARAJAN, PRAVEEN; Mohamad Firdaus Ab Aziz (Applied Information Technology And Computer Science, 2026)
EasyService is a PHP-based car service booking system designed to address the challenges of inefficient booking processes, customer satisfaction, and resource management in the car service industry. This project evaluates how the system simplifies service bookings, enhances customer experience, and improves service management for small and medium-sized businesses. The main goal is to create a web-based platform that ensures smooth bookings, collects real-time customer feedback, and guarantees timely services. Built with PHP, MySQL, and other web tools, the system's usability was tested through user feedback, focusing on satisfaction, error rates, and task completion speed. Results show that EasyService reduces booking times, encourages customer feedback, and increases efficiency, leading to higher user satisfaction. This project demonstrates the potential of technology to streamline traditional car service operations. Future developments could include features like predictive maintenance and mobile device support, further enhancing accessibility and innovation.